2010
DOI: 10.3748/wjg.v16.i32.4072
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of cancer-testis antigen mRNA in peripheral blood from hepatocellular carcinoma patients

Abstract: Detecting MAGE-1, SSX-1 and CTp11 mRNA in PBMC improves the total diagnostic rate of HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…CTp11 mRNA was expressed in 25-30% of the melanoma and bladder carcinoma cell lines tested, while only 2 of the 29 other tumor cell lines were positive. Recent studies reported a high frequency of CTp11 expression in 56.2% of HCC tissues and 31.1% of PBMC from HCC patients (31). In our study, CTp11 was expressed in 62% of HCC cell lines and 11% of HCC tissues.…”
Section: Discussionsupporting
confidence: 65%
“…CTp11 mRNA was expressed in 25-30% of the melanoma and bladder carcinoma cell lines tested, while only 2 of the 29 other tumor cell lines were positive. Recent studies reported a high frequency of CTp11 expression in 56.2% of HCC tissues and 31.1% of PBMC from HCC patients (31). In our study, CTp11 was expressed in 62% of HCC cell lines and 11% of HCC tissues.…”
Section: Discussionsupporting
confidence: 65%
“…Although 30%-40% of primary liver cancer is negative for AFP (29), it is still a sensitive tumor marker for the detection of HCC and a useful predictive factor due to its specificity for patient survival after locoregional or systemic treatment in HCC (30,31). A South Korean study reported that AFP normalization within 3 months after SBRT was a prognostic surrogate for OS and PFS in patients with small HCC (32).…”
Section: Discussionmentioning
confidence: 99%
“…Detection of serum alpha-fetoprotein (AFP) is used in clinical follow-up for high-risk population screening and cancer patients. Although 30% ~ 40% of patients have negative AFP detection in HCC of China [ 14 ], due to its characteristics of high specificity, it is still of significant value in clinical examination. In this study, the selected patients had AFP levels greater than 400 ng/mL before the first TACE treatment.…”
Section: Discussionmentioning
confidence: 99%